2021
DOI: 10.1098/rspb.2021.0690
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variation in the wintering associations of an alpine bird

Abstract: Many animals make behavioural changes to cope with winter conditions, being gregariousness a common strategy. Several factors have been invoked to explain why gregariousness may evolve during winter, with individuals coming together and separating as they trade off the different costs and benefits of living in groups. These trade-offs may, however, change over space and time as a response to varying environmental conditions. Despite its importance, little is known about the factors triggering gregarious behavi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…, quantity, distribution), which can have social implications in the short-term ( i.e., within-season) by influencing fission–fusion group dynamics (see e.g. , del Mar Delgado et al., 2021 ). In the long-term ( i.e., between years), environmental changes can potentially shape population structure ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…, quantity, distribution), which can have social implications in the short-term ( i.e., within-season) by influencing fission–fusion group dynamics (see e.g. , del Mar Delgado et al., 2021 ). In the long-term ( i.e., between years), environmental changes can potentially shape population structure ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, rain-on-snow events, which lead to rapid freezing and thawing, can increase bird mortality, degrade suitable habitats, and block food source acquisition [53]. In wintering white-winged snowfinch (Montifringilla nivalis nivalis), flock sizes have decreased due to climate warming [54]. Multispecies models have also found that birds tend to select areas with intermediate precipitation levels in winter [55].…”
Section: Wintering Whooper Swan Habitat Selection At the Landscape Scalementioning
confidence: 99%